The Influence of Self-Efficacy and Self-Esteem on Intention to Stay through Motivation and Employee Engagement among Generation Z in Malang City Startups - Muhizan Tamimi; Heri Pratikto; Sopiah Sopiah (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze how self-efficacy and self-esteem influence Generation Z employees’ intention to stay (ItS) in Malang City startups through motivation and employee engagement. Using a quantitative approach with PLS-SEM mediation analysis, data were collected from 200 Gen Z employees (aged 18–27) across startups at Malang via validated Likert-scale questionnaires. Results reveal that self-efficacy directly enhances employees’ intention to stay, motivation, and engagement, whereas self-esteem bolsters motivation and engagement but does not directly influence their intention to remain. Interestingly, high engagement can paradoxically reduce the intention to stay, as it often leads to burnout from excessive workloads and insufficient rewards. Furthermore, motivation successfully mediates the relationship between both self-efficacy and self-esteem on the intention to stay, a mediating role that engagement does not fulfill. Novelty lies in integrating Social Cognitive Theory and Social Exchange Theory to resolve prior inconsistencies in the understudied context of Gen Z in Indonesian startups. Startups can boost Gen Z retention by building self-efficacy through structured training, implementing performance-based rewards, and enforcing strict work-life balance policies to prevent engaged employees from burning out. This study offers a theoretical contribution by integrating Social Cognitive and Social Exchange Theories to reveal the paradoxical pathway where employee engagement reduces retention, while confirming motivation’s crucial mediating role in the Indonesian Gen Z startup context.